2017
DOI: 10.31767/nasoa.3.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

The Models of Distance Forms of Learning in National Academy of Statistics, Accounting and Audit

Abstract: Finding solutions to the problems faced by the Ukrainian education system require an adequate organizing structure for education system, enabling for transition to the principle of life-long education. The best option for this is the distance learning systems (DLS), which are considered by leading Ukrainian universities as high-performance information technologies in modern education, envisaged by the National Informatization Program, with the goals of reforming higher education in Ukraine in the context of jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Results analysis of practicality data obtained from student responses above resulted in a percentage of 94 percent in the convenient category. In line with research conducted by (Deryhlazov et al, 2017), web-based learning media using moodle met applicable criteria as seen from the results of student questionnaires with excellent categories. The development of web-based learning media with Moodle can function as two-way interactive learning media or can also be carried out synchronously and provide discussion features by creating interaction, feedback, debate, and online collaborative work, both open and private.…”
Section: Product Distributionsupporting
confidence: 74%
See 1 more Smart Citation
“…Results analysis of practicality data obtained from student responses above resulted in a percentage of 94 percent in the convenient category. In line with research conducted by (Deryhlazov et al, 2017), web-based learning media using moodle met applicable criteria as seen from the results of student questionnaires with excellent categories. The development of web-based learning media with Moodle can function as two-way interactive learning media or can also be carried out synchronously and provide discussion features by creating interaction, feedback, debate, and online collaborative work, both open and private.…”
Section: Product Distributionsupporting
confidence: 74%
“…Furthermore, moodle research is associated with the flex model conducted by (Deryhlazov et al, 2017;Tirza, 2021), making it possible for students to enter the classroom digitally when learning online. Moodle is flex based to provide easy access, effectively helping increase student knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also revealed that the student's capacity for mathematical representation was significantly improved by the Auditory Intellectual Repetition (AIR) approach (Ikawati & Kowiyah, 2021). Representation is closely related to the Auditory Intellectually Repetition (AIR) learning model, a learning model that focuses on active student learning and contributes to the development of their knowledge both alone and in groups (Deryhlazov et al, 2017). The Auditory Intellectually Repetition (AIR) learning model is said to be successful because it emphasizes three learning factors, namely Auditory (Christine et al, 2020), Intellectual (Septian, 2020), and Repetition (Song & Kim, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It can also be used to understand the meaning of a data set, starting from grouping it (Astuti, 2021), processing it, and serving it. To present statistical data, software to obtain conclusions from the results of the analysis (Deryhlazov et al, 2017;Ferguson, 2020).…”
Section: Introductionmentioning
confidence: 99%